2013
DOI: 10.1111/plb.12012
|View full text |Cite
|
Sign up to set email alerts
|

Leaf functional trait variation associated with salt tolerance in perennial ryegrass

Abstract: Salinity is one of major environmental stresses that dramatically threaten plant growth, and variations in genetic structure and functional traits have important effects on the salt tolerance of perennial ryegrass (Lolium perenne L.). The objectives of this study were to: (i) assess the inter-clonal variation of functional traits of accessions among geographic groups or between wild and commercial groups in response to salt stress; (ii) develop a mathematical model to effectively assess salt tolerance of peren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…The salt tolerance of both cultivars has been identified in our previous study (Hu et al. ). The pots were watered daily and fertilized weekly with half‐strength Hoagland's solution (Hoagland and Arnon ).…”
Section: Methodsmentioning
confidence: 72%
“…The salt tolerance of both cultivars has been identified in our previous study (Hu et al. ). The pots were watered daily and fertilized weekly with half‐strength Hoagland's solution (Hoagland and Arnon ).…”
Section: Methodsmentioning
confidence: 72%
“…The other research reported that the effect on parameters of photosynthetic efficiency in perennial ryegrass "Roadrunner" was less than that in "Nira" under salt stress condition [6]. Moreover, the highest salt tolerance accessions were from the European group, wild accessions and exhibited more variation in functional traits and salt tolerance than commercial cultivars [90]. Some other strategies can also improve the salt-tolerance in perennial ryegrass.…”
Section: Responses Of Salt Stress In Perennial Ryegrassmentioning
confidence: 97%
“…Responses of plants to salinity stress occur mainly through two distinct phases over time: osmotic-changing and ion specific phases [87][88][89]. Like other turfgrasses, salt stress caused morphology, physiology, molecular changes in growth and development of perennial ryegrass, such as TQ LFW, LED, and RWC of perennial ryegrass decreasing after exposure to salinity [89,90]. The alterations of morphological characteristics of turfgrass under salt stress are derived from the changes of physiological traits such as cell membrane stability [14].…”
Section: Responses Of Salt Stress In Perennial Ryegrassmentioning
confidence: 99%
“…u(xj) is the subordinate function value of the jth evaluation index. D indicates the integrated values for salt tolerance in Italian ryegrass [Equation (13)]. The lower the value of D, the higher the salt tolerance.…”
Section: Evaluation Of Salt Tolerance By An Integrated Evaluation Systemmentioning
confidence: 99%
“…In addition to rapid growth, high dry matter production and high forage quality are desirable characteristics for promising forage varieties. In grass species, saline environments induce adaptive changes in morphological, physiological, and biochemical traits of plants, including changes in growth rate, osmotic adjustment, photosynthesis efficiency, and nutrition value [12][13][14]. Plant adaptation to salt is a complex phenomenon.…”
Section: Introductionmentioning
confidence: 99%